Exosomal mir-126-3p derived from endothelial cells induces ion channel dysfunction by targeting RGS3 signaling in cardiomyocytes: a novel mechanism in Takotsubo cardiomyopathy - Fan, Xuehui; Yang, Guoqiang; Wang, Yinuo; Shi, Haojie; Nitschke, Katja; Sattler, Katherine; Abumayyaleh, Mohammad S. A.; Cyganek, Lukas; Nuhn, Philipp; Worst, Thomas; Liao, Bin; Dobreva, Gergana; et al. (Stem cell research & therapy, 2025)
Takotsubo cardiomyopathy (TTC) is marked by an acute, transient, and reversible left ventricular systolic dysfunction triggered by stress, with endothelial dysfunction being one of its pathophysiological mechanisms. However, the precise molecular mechanism underlying the interaction between endothelial cells and cardiomyocytes during TTC remains unclear. This study reveals that exosomal miRNAs derived from endothelial cells exposed to catecholamine contribute to ion channel dysfunction in the setting of TTC.
Gesehen am 05.09.2025